2019
DOI: 10.3390/coatings9080475
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Urea Formaldehyde @ Epoxy Resin Microcapsule on Waterborne Wood Coatings

Abstract: Urea formaldehyde @ epoxy resin microcapsules were prepared by two steps in situ polymerization, and the morphology and composition of microcapsules with different mass ratios of core to wall material were examined by scanning electron microscopy (SEM) and infrared (IR) spectroscopy. The microcapsules were added to the waterborne wood coatings to explore the effect of microcapsules on the properties of coatings and their self-repairing characteristics, and the gloss, hardness, adhesion, and impact resistance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…The coating was compared with the performance of the waterborne coating with epoxy resin microcapsules [ 31 ]. According to Table 9 , it can be found that the gloss of the two kinds of coating with microcapsules was similar, but the hardness and impact resistance of the coating with epoxy resin microcapsules were relatively high, while the adhesion was low.…”
Section: Resultsmentioning
confidence: 99%
“…The coating was compared with the performance of the waterborne coating with epoxy resin microcapsules [ 31 ]. According to Table 9 , it can be found that the gloss of the two kinds of coating with microcapsules was similar, but the hardness and impact resistance of the coating with epoxy resin microcapsules were relatively high, while the adhesion was low.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with the WUV coating, the ZnSt2/WUV coating had the property of superhydrophobicity. out and weighed after a period of time, and the water absorption before and after modification was calculated by using Equation 1: (1) where mbi and mai represent the film weights before and after absorbed water, respectively [15].…”
Section: Contact Angle (Ca) Testmentioning
confidence: 99%
“…calculated by using Equation 1: (1) where mbi and mai represent the film weights before and after absorbed water, respectively [15].…”
Section: Znst2/wuvmentioning
confidence: 99%
See 1 more Smart Citation
“…The coating was heated slowly, the surface temperature of the coating was measured with a temperature sensor, and the chroma value of the coating was measured with a colorimeter to determine the temperature dependence of the result. The gloss, impact resistance, and adhesion of finish films were measured according to reference [16]. The gloss of the finish film was tested using a 3nh smart gloss meter (produced by 3NH Technology Co., Ltd., Shenzhen, China).…”
Section: Testing and Characterizationmentioning
confidence: 99%